Multivariable Analysis of Primary Care Physician Adherence to Guideline-recommended Pharmacotherapy of Stable Coronary Artery Disease - S. K. Zyryanov; S. B. Fitilev; A. V. Vozzhaev; I. I. Shkrebniova (Рациональная фармакотерапия в кардиологии)
Aim. To study predictors of primary care physician adherence to guideline-recommended pharmacotherapy of stable coronary artery disease.Material and methods. This pharmacoepidemiologic cross-sectional study was conducted in primary care setting of Moscow. 805 patients (mean age 68.9±9.9 years, males 51.4%) with established stable coronary artery disease (SCAD) were included. Demography, medical history, prescribed pharmacological treatment data were obtained. Physician adherence to guideline-recommended pharmacotherapy (GRP) of SCAD was evaluated based on the Class I guideline recommendations. Pharmacotherapeutic guideline adherence index (PGAI) was introduced as composite quality indicator, calculated in line with “all-or-none” rule and in regard with documented contraindications. To search for predictors of adherence the patient population was divided in two groups by level of physician adherence measured by PGAI. Statistical analysis was performed by IBM SPSS Statistics 16.0, the level of statistical significance was set at p<0.05.Results. The prescription rates of essential drug therapies of SCAD (regarding contraindications) were quite adequate: beta-blockers/calcium channel blockers – 90,1%, acetylsalicylic acid/clopidogrel/oral anticoagulants – 95,7%, statins/ezetimibe – 86,3%, angiotensin-converting enzyme inhibitors/angiotensin II receptor blockers – 87,6%. 82,9% (n=667) of patients were prescribed treatment for SCAD in compliance with the guidelines. Suboptimal pharmacotherapy was identified in 17,1% (n=138) of patients. These groups were similar in sex distribution (males 50,4 vs. 56,5%; p=0,188). Mean age tended to be lower in GRP adherent group (68,5±9,9 vs. 70,6±10,0 years; p=0,052). Bivariable analysis showed that good adherence to guideline-recommended pharmacotherapy was associated with higher prevalence of stable angina (66,4 vs. 53,6%; p=0,004), arterial hypertension (93,3 vs. 79,7%; p<0,001) and dyslipidemia (21,4 vs. 9,4%; p<0,001) and with lower prevalence of myocardial infarction (48,1 vs. 67,4%; p<0,001). Logistic multivariable regression model (gender, age, 6 medical history variables) identified 6 patient-related factors that were significantly associated with physician adherence to guideline-recommended pharmacotherapy: age (odds ratio [OR] 0,97; 95% confidence interval [CI] 0,95-0,99; p=0,009), arterial hypertension (OR 3,89; 95%CI 2,19-6,90; p<0,001), dyslipidemia (OR 2,31; 95%CI 1,23-4,34; p=0,009), chronic heart failure (OR 1,95; 95%CI 1,06-3,61; p=0,032), revascularization (OR 2,14; 95%CI 1,33-3,45; p=0,002), myocardial infarction (OR 0,28; 95%CI 0,16-0,48; p<0,001).Conclusion. Primary care cardiologist adherence to guideline-recommended pharmacotherapy of SCAD was satisfactory evaluated as 82,9% by composite indicator PGAI. Arterial hypertension, heart failure, dyslipidemia и revascularization were predictors of better physician adherence. History of myocardial infarction and older age were risk factors of non-adherence. Identification of patient-related factors associated with underperformance may facilitate tailoring quality improvement interventions in primary care of coronary patients.